Updated guidelines (2021) for management and follow-up of asthmatic patients of the French Society of Pneumology (SPLF) and the French Society of Pediatric Pneumology and Allergology (SP2A). Short version - Raherison-Semjen, Chantal; Guilleminault, Laurent; Billiart, Isabelle; Chenivesse, Cécile; De Oliveira, Annie; Izadifar, Armine; Lorenzo, Alain; Nocent, Cécilia; Oster, Jean-Philippe; Padovani, Mireille; Perez, Thierry; Russier, Maud; et al. (Respiratory medicine and research, 2022)
The therapeutic management strategy is based on the regular evaluation of the control of asthmatic disease, with an effective minimum dose research and the assessment of environmental factors, not to mention the important place of therapeutic education. These professional recommendations relate to the management and follow-up of adult and adolescent asthma patients aged 12 and over. The recommendations answer the following questions: 1. How to make the initial diagnosis of asthma? 2. What allergological check-up should be done in asthmatics 3. How to manage an asthma exacerbation? 4. How to manage difficult asthma? 5. What therapeutic strategies? 6. How to manage a woman's asthma during pregnancy? 7. Environmental factors in asthma management review